Continuous culture of Cryptosporidium parvum using hollow fiber technology. Issue 1 (January 2016) - Morada, Mary; Lee, Sangun; Gunther-Cummins, Leslie; Weiss, Louis M.; Widmer, Giovanni; Tzipori, Saul; Yarlett, Nigel
Graphical abstract: Highlights: Cryptosporidium parvum was cultured in vitro for >1 month. The system employed HCT-8 3D cultures grown on hollow fibers. This biphasic system permitted a separate host cell and parasite nutrient supply. Parasite nutrients included a lipid mix and a redox buffer. Abstract: Diarrheal disease is a leading cause of pediatric death in economically low resource countries. Cryptosporidium spp. are the second largest member of this group and the only member for which no treatment exists. One of the handicaps to developing chemotherapy is the lack of a reproducible long-term culture method permitting in vitro drug screening beyond 48 h. We have adapted the well-established hollow fiber technology to provide an environment that mimics the gut by delivering nutrients and oxygen from the basal layer upwards while allowing separate redox and nutrient control of the lumen for parasite development. Using this technique, oocyst production was maintained for >6 months, producing approximately 1 × 10 8 oocysts ml −1 day −1, compared with 48 h with a yield of 1 × 10 6 oocysts ml −1 in two-dimensional cultures. Oocysts, after 4 and 20 weeks in culture, produced a chronic infection in a TCR-α-deficient mouse model. In vivo infectivity of oocysts was confirmed using oocysts from a 6 week culture in a dexamethasone immunosuppressed mouse model.